PENGEMBANGAN MEDIA VIDEO BERBASIS CAPCUT MATA PELAJARAN IPAS MATERI ORGAN PERNAPASAN PADA SISWA KELAS 5 SDN DUKUH KUPANG V SURABAYA - Yuanta, Friendha; Ramadamayanti, Risanda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning Natural and Social Sciences (IPAS) material on human respiratory organs in elementary school requires students to understand abstract concepts that are difficult to observe directly. The use of CapCut-based video media is expected to facilitate student understanding through interactive visualization and audio. The media was developed using the ADDIE model. The results of validation by media experts and subject matter experts were 91.25% and 85%, respectively, which is considered valid. Small, medium, and large group trials obtained acceptable scores of 80%, 89.5%, and 91.9%. Analysis of learning outcomes showed an increase in the average score from 88 (pre-test) to 97.2 (post-test). This media is effective and feasible to use to improve students' understanding interactively and contextually.